2016
DOI: 10.1371/journal.pone.0167540
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Differently Located Colorectal Cancers Support Proximal and Distal Classification: A Population-Based Study of 57,847 Patients

Abstract: BackgroundIt has been suggested that colorectal cancer be regarded as several subgroups defined according to tumor location rather than as a single entity. The current study aimed to identify the most useful method for grouping colorectal cancer by tumor location according to both baseline and survival characteristics.MethodsCases of pathologically confirmed colorectal adenocarcinoma diagnosed from 2000 to 2012 were identified from the Surveillance, Epidemiology, and End Results database and categorized into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 37 publications
6
64
1
1
Order By: Relevance
“…While incomplete colonoscopy was reported in some studies on interval CRC to be > 15%, the cecal intubation rate or complete colonoscopy rate of our center was more than 95% according to our latest colonoscopy registry (unpublished data). It is also important to know that distal cancer is still more prevalent than proximal cancer in Chinese patients (56.5% vs 43.5%) that may account for the higher proportion of distal PCCRC‐3y as well . As for our center, distal CRC constituted 68.6% of all CRC cases in 2017 (unpublished data).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While incomplete colonoscopy was reported in some studies on interval CRC to be > 15%, the cecal intubation rate or complete colonoscopy rate of our center was more than 95% according to our latest colonoscopy registry (unpublished data). It is also important to know that distal cancer is still more prevalent than proximal cancer in Chinese patients (56.5% vs 43.5%) that may account for the higher proportion of distal PCCRC‐3y as well . As for our center, distal CRC constituted 68.6% of all CRC cases in 2017 (unpublished data).…”
Section: Discussionmentioning
confidence: 86%
“…It is also important to know that distal cancer is still more prevalent than proximal cancer in Chinese patients (56.5% vs 43.5%) that may account for the higher proportion of distal PCCRC-3y as well. 32 As for our center, distal CRC constituted 68.6% of all CRC cases in 2017 (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…However, the subgroup analysis showed a significant better survival in stage III LCC (HR, 1.12; 95% CI, 1.06‐1.18; P < 0.001), but worse survival in stage II LCC (HR, 0.92; 95% CI, 0.87‐0.97; P = 0.001) compared with RCC . The discrepancy in the survival by stage was reported recently in both Eastern and Western countries . Despite variation in the reported results, most authors observed a poor survival for RCC in stage III cases.…”
Section: Discussionmentioning
confidence: 82%
“…For the reasons, many authors have indicated RCC as a disease distinct from LCC. Most studies have shown that survival with RCC is poorer than that with LCC for either primary lesions or cancer with metastasis . However, these previous studies mainly analyzed patients with primary colon cancer undergoing resection or patients with metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation